Reflection of world views in the speech discourse of fishermen community - Fuad, Akhmad Dzukaul; Santoso, Anang; Pratiwi, Yuni; Roekhan, Roekhan; Tamphu, Sainee (citeus, 2025)
Language reflects the logical structure of reality and shapes how speakers perceive themselves and their surroundings. Language relativity reinforces the connection between language and cultural behavior. This study examines the worldview of the Puger fishermen community, a speech community within Jember Pandhalungan culture, through their language use and discourse patterns. Their linguistic repertoire, shaped by coastal life in south Jember, East Java, influences their speech behavior. Using ethnographic communication methods, this study classifies and analyzes their speech discourse based on six worldview elements. Each discourse conveys meaning that defines their identity and perceptions of outsiders. Puger fishermen see themselves as brave, consistent, innovative, adaptive, introspective, and egalitarian. They regard the sea as their source of life and livelihood, emphasizing harmony between their lives and the ocean. Their speech discourse also reflects a value system guiding their way of life. They interpret and implement these values to create a balanced existence, aligning with the philosophy of memayu hayuning bawana—preserving harmony in the world. Through their language, the Puger fishermen demonstrate a deep connection between cultural identity, worldview, and daily life.